Photolithographic Microfabrication of Microbatteries for On-Chip Energy Storage - Yuan Ma; Sen Wang; Zhong-Shuai Wu (Nano-Micro Letters)
Highlights The fundamental principles and step-by-step procedures of photolithography are introduced, and a nuanced understanding of its operational mechanisms and the criteria for photoresist selection is offered. Various specific roles that photolithography plays in microbatteries (MBs) fabrication, including templates for 2D and 3D micropatterns, MB active components, and the sacrificial layer for constructing micro-Swiss-roll structure, are elaborated. The challenges and future directions of MBs fabricated using photolithography, including materials selection, packaging techniques, application, and performance evaluation, are discussed.